Psychological interventions for post-traumatic stress disorder and comorbid substance use disorder: A systematic review and meta-analysis. (June 2015) - Roberts, Neil P.; Roberts, Pamela A.; Jones, Neil; Bisson, Jonathan I.
Abstract: Co-morbid post-traumatic stress disorder (PTSD) and substance use disorder (SUD) are common, difficult to treat, and associated with poor prognosis. This review aimed to determine the efficacy of individual and group psychological interventions aimed at treating comorbid PTSD and SUD, based on evidence from randomised controlled trials. Our pre-specified primary outcomes were PTSD severity, drug/alcohol use, and treatment completion. We undertook a comprehensive search strategy. Included studies were rated for methodological quality. Available evidence was judged through GRADE. Fourteen studies were included. We found that individual trauma-focused cognitive–behavioural intervention, delivered alongside SUD intervention, was more effective than treatment as usual (TAU)/minimal intervention for PTSD severity post-treatment, and at subsequent follow-up. There was no evidence of an effect for level of drug/alcohol use post-treatment but there was an effect at 5–7 months. Fewer participants completed trauma-focused intervention than TAU. We found little evidence to support the use of individual or group-based non-trauma-focused interventions. All findings were judged as being of low/very low quality. We concluded that there is evidence that individual trauma-focused psychological intervention delivered alongside SUD intervention can reduce PTSD severity, and drug/alcohol use. There is very little evidence to support use of non-trauma-focused individual or group-based interventions. Highlights: Comorbid PTSD and SUD are difficult to treat. Drop-out from treatment is high. There is evidence of benefit from approaches that include trauma-focused intervention. There is little evidence for non-trauma-focused approaches at present. The quality of current evidence is low.